Villon – A Tool for Simulation of Operation of Transportation Terminals - Adamko, Norbert; Marton, Peter (Communications - Scientific letters of the University of Zilina, 2008)
The paper deals with the modelling of transportation terminals operation (e.g. marshalling yards, factories, train care centres, airports, etc.) utilizing generic simulation tool Villon, which was developed using agent based simulation architecture ABAsim. Villon is complete simulation tool providing support for creation, configuration, experimentation and results evaluation tasks connected with simulation modelling of transportation terminals. Villon’s unique features like its flexibility, detailed microscopic modelling of operation of various types of terminals, flowchart driven definition of operational procedures, user interaction, selection of decision strategies, 3D animation output and model creation process are explained. Project references and problems that can be addressed using presented simulation tool are also mentioned.